Cost estimating and information management for engineering modification business - Garcia Fornieles, J. (Cranfield University, 2002)
Complex Engineering Product (CEP) modification businesses cover a wide range of project types. The diversity of the projects and the interaction of different stakeholders introduce difficulties in cost estimating. Also, the uncertainties and unknowns typical of these projects induce significant changes of scope as the project develops. A new approach for historical cost data re-use has been applied in this study that addresses the disjoints in business processes and data typical of complex engineering organisations. A model has been developed to make explicit and integrate the scope and cost in CEP modification projects. To integrate the different project stakeholders views while maintaining a common project vision the concept of the integrated Work Breakdown Structure (iWBS) has been developed. The concept is based on the combination of a project template, a rigid and a f1exiDle part for a project WBS. The iWBS allows for the flexibility required by the different people when carrying out their job and enhances the communication by allowing rapid response to changes. The data structure supports cost data re-use at two levels,' from project to project and between different phases of a project. A bid process has been defined to structure the business decision activities and participants, identifying explicit decision points where changes can affect the data structure. Thus, dealing with the changes typical of CEP modification projects. The study has used a case study approach based on the aircraft modification industry where detailed learning has been presented. The study contributes to a better understanding of CEP modifications and cost estimating for this type of businesses.